Origin and age of Australian Chenopodiaceae - Kadereit, Gudrun; Gotzek, Dietrich; Jacobs, Surrey; Freitag, Helmut (Organisms diversity & evolution, 2005)
We studied the age, origins, and possible routes of colonization of the Australian Chenopodiaceae. Using a previously published rbcL phylogeny of the Amaranthaceae–Chenopodiaceae alliance (Kadereit et al. 2003) and new ITS phylogenies of the Camphorosmeae and Salicornieae, we conclude that Australia has been reached in at least nine independent colonization events: four in the Chenopodioideae, two in the Salicornieae, and one each in the Camphorosmeae, Suaedeae, and Salsoleae. Where feasible, we used molecular clock estimates to date the ages of the respective lineages. The two oldest lineages both belong to the Chenopodioideae ( Scleroblitum and Chenopodium sect. Orthosporum/ Dysphania) and date to 42.2–26.0 and 16.1–9.9 Mya, respectively. Most lineages (Australian Camphorosmeae, the Halosarcia lineage in the Salicornieae, Sarcocornia, Chenopodium subg. Chenopodium/ Rhagodia, and Atriplex) arrived in Australia during the late Miocene to Pliocene when aridification and increasing salinity changed the landscape of many parts of the continent. The Australian Camphorosmeae and Salicornieae diversified rapidly after their arrival. The molecular-clock results clearly reject the hypothesis of an autochthonous stock of Chenopodiaceae dating back to Gondwanan times. Instead, they indicate that most lineages arrived in Australia via long-distance dispersal. Some lineages (e.g. the Halosarcia lineage) may have used the Indonesian archipelagos as stepping stones. The authors are aware that estimates of diversification times using a molecular clock can be subject to considerable levels of error. Our estimates of the age of Australian chenopod lineages based on three alternative fossils were made independently from any knowledge about shifts in climatic and geographical conditions in Australia during the times of arrival. In most cases, however, the paleoclimatic scenario indicates habitat shifts suitable for the respective chenopod colonizer, which corroborates our findings and provides a plausible scenario.